Identity challenges of women leaders: Antecedents and consequences of identity interference - Natalia Karelaia; Laura Guillén (European School of Management and Technology (ESMT), 2011)
We explore the antecedents and consequences of women leaders' identity interference related to the perceived conflict between their roles as both women and leaders. Drawing on identity development and organizational demography research, we propose that leadership experience reduces women leaders' identity interference, whereas women's numerical underrepresentation in organizations exacerbates it. Moreover, we hypothesize that identity processes related to collective self-esteem - personal regard for one's collective identity and the perception of others' views of it - mediate these effects. A sample of 722 women leaders representing a diverse range of countries and industries supported our hypotheses. We also demonstrate that identity interference reduces the psychological well-being of women leaders and undermines their affective motivation to lead. In contrast, perceived conflict between leader and female identities enhances women's sense of duty to assume leadership roles. Importantly, women leaders' personal regard for their female identity buffers the detrimental effect of identity interference on life satisfaction. We discuss the implications of our results for women's advancement in organizations and the development of their identity as leaders.
urn:nbn:de:101:1-201201176387
Keywords: 650; women leaders; identity interference; collective self-esteem; well-being; motivation to lead; leader development; organizational demography; Weibliche Führungskräfte; Persönlichkeitspsychologie; Führungsstil; Verhalten in Organisationen